2011
DOI: 10.1160/th10-07-0480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the time of diagnosis on outcome in patients with acute venous thromboembolism

Abstract: SummaryThe influence of the day of diagnosis (weekends vs. weekdays) on outcome in patients with acute venous thromboembolism (VTE) has not been thoroughly studied. We used the RIETE database to compare the clinical characteristics, treatment details, and mortality rate at 7 and 30 days, of all patients diagnosed with acute VTE on weekends versus those diagnosed on weekdays. Up to January 2010, 30,394 patients were included in RIETE, of whom 5,479 (18%) were diagnosed on weekends. Most clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…[15][16][17][18] The Registro Informatizado Enfermedad TromboEmbolica (RIETE) is a large prospective registry initiated to address these unmet needs and has been enrolling patients with objectively confirmed VTE since 2001. Several of the resultant studies have provided a better understanding of the epidemiology, 19,20 common treatment patterns, 21,22 and outcomes 23,24 of patients with VTE and the key understudied clinical subgroups. [25][26][27] In response to continued and expanding investigations from RIETE, herein we provide an overview of the design, methodology, possible and future directions of the registry.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The Registro Informatizado Enfermedad TromboEmbolica (RIETE) is a large prospective registry initiated to address these unmet needs and has been enrolling patients with objectively confirmed VTE since 2001. Several of the resultant studies have provided a better understanding of the epidemiology, 19,20 common treatment patterns, 21,22 and outcomes 23,24 of patients with VTE and the key understudied clinical subgroups. [25][26][27] In response to continued and expanding investigations from RIETE, herein we provide an overview of the design, methodology, possible and future directions of the registry.…”
Section: Introductionmentioning
confidence: 99%
“…Our search strategy identified 12 investigations for the analysis (Supplementary File 2, http://links.lww.com/JCM/A459), 3–14 based on 1 782 385 patients with acute pulmonary embolism (Table 1). Quality assessment showed that all studies were of moderate–high quality according to the NOS scale.…”
Section: Resultsmentioning
confidence: 99%
“…It started in Spain in 2001, and 6 years later the database was translated into English aimed to expand the Registry to other countries. Data from this registry have been used to evaluate outcomes after acute PE, such as the frequency of recurrent VTE, bleeding and mortality, and risk factors for these outcomes [20][21][22][23]. In the current study, we used the RIETE database to compare the 30-day mortality of patients with acute PE presenting with SBP levels ≥ 90 mm Hg, according to the presence or absence of RA dilatation on TTE at baseline.…”
Section: Introductionmentioning
confidence: 99%